Introduction to crime scene photography - Robinson, Edward M. (Oxford : Academic Press, 2013)
From the author of Crime Scene Photography, 2nd Edition, this introductory text serves as a detailed nuts-and-bolts version of its big brother, currently required reading for certification by the IAI Crime Scene Certification Board. Written for those just beginning their educations related to crime scene investigations, Introduction to Crime Scene Photography shares many of the features of the advanced text. This text initiates the novice to all the essentials of basic crime scene photography techniques. And, it provides a smooth transition to the more complicated and advanced techniques found in the larger text. The beginning of the book deals with basic theory and science of photography. This acquaints the reader with knowledge required to take superior photographs using composition, lighting and focus. Then follows photographing the crime scene, including specialty types of photography such as ultraviolet, fluorescence and infrared, going digital, using photos specifically to document bodies, wounds, and other related components to the crime scene. Also included are two chapters on the legal aspects of forensic photography and digital image processing.
Keywords: Crime scenes; Evidence, Criminal; Legal photography